Pengaruh Peran Orang Tua terhadap Pemenuhan Kebutuhan Gizi Anak Usia 3-4 Tahun TPA Asmaul Husna - Elva M. Sumirat; Nur Risha Djumaat; Nurlatifa Olola; Salwa Nevara Yusuf; Tiara Baulu; Rahmayanti Datunsolang; Nida Tazkia Saleh (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
This study aims to analyze the influence of parental roles on fulfilling the nutritional needs of children aged 3–4 years at the Asmaul Husna Daycare (TPA) in Gorontalo. The study used a quantitative design with a cross-sectional approach and involved 60 parents as respondents. The role of parents was measured through their active involvement as educators, motivators, and facilitators in fulfilling children's nutritional needs. The results showed that 80% of children whose parents played an active role had good nutritional status based on normal weight for age and height for age indicators. Conversely, in the group of less active parents, only 36% of children achieved good nutritional status. The Chi-square test showed a significant relationship between parental roles and children's nutritional status (p < 0.05). The table data shows a clear disparity, with 32 well-nourished children coming from the active role group, while 14 children with poor nutritional status came from the passive role group. These findings emphasize the importance of monitoring dietary patterns, providing nutritious supplies, and collaboration between parents and the TPA in reducing the risk of malnutrition and stunting. Furthermore, parental involvement contributes to improved immunity, cognitive development, and the formation of long-term healthy eating habits. This study recommends holding nutrition workshops for parents as part of a sustainable TPA program.